Un transhumanisme « à mains nues » - Sébastien Dalgalarrondo; Tristan Fournier (Revue d'anthropologie des connaissances)
This article aims to analyze the recent development of the fasting market in France, looking at its promises as well as the ideologies in which it takes root. The data collected come from a content analysis of the websites that promote fasting courses, interviews conducted with the heads of marketing networks, and an extensive literature review (gray and scientific literature). After having rebuilt the socio-historical trajectory of this promise, defined the online offering, and described the rhetoric used by the promoters, the authors identify an argumentative assemblage that combines alternative and scientistic discourses, and that is made of three lines: ascetism, politics, and self-exploration. This original assemblage enables us to understand the contemporary practice of fasting as a self-optimization technique from which one does more with less: transhumanism “with bare hands.”